Human health risk assessment of metal contamination through consumption of fish - Nurul Amirah, Mat Nawi; Afiza, Abdullah Suhaimi; Wan Faizal, Wan Ishak; Nurliyana, Moh Hussin; Laili, Sengut (Science and Education Publishing, 2013)
The progress of industries has led to the increased of pollutants emission into the ecosystems. One of the most common pollutants is heavy metals. This research deals with human health risk assessment of metal contamination through the consumption of fish at selected river in Kuantan, Pahang. The objective of this research is to determine the concentration of Cu, Pb and Cd contaminant in fish. This research describes the heavy metal experiment analysis and health risk assessment. Inductively Coupled Plasma Membrane System (ICP-MS) was used to determine the concentration of heavy metals in fish. The average concentration of Cu, Pb and Cd in three locations are approximately 0.0205µg/g, 0.0145µg/g and 0.0004µg/g. Target Hazard Quotient (THQ) was used in the health risk assessment to determine carcinogenicity of the sample. The result shows that the concentration and THQ of all metal studied (Cu, Pb, Cd) are less than 1; signified that a daily exposure at this level is unlikely to cause any adverse effects during a person lifetime.